Design of high performance low-dropout regulators for on-chip applications - Chong, Sau Siong (2014)
The growing portable and battery powered devices have driven the power management circuits to consume as low power as possible so as to prolong the operation life of the devices. Low-dropout (LDO) regulators are important building blocks in power management unit which provides majority or all power sources in a system chip. This work focuses on the circuit design techniques for high-performance regulators for on-chip applications.